Long-term follow-up study of clear cell papulosis - Tseng, Fang-Wen; Kuo, Tseng-Tong; Lu, Pei-Hsuan; Chan, Heng-Leong; Chan, Ming-Jing; Hui, Rosaline Chung-Yee (Journal of the American Academy of Dermatology, 2010)
Clear cell papulosis (CCP) was described as a new entity in 1987. Since then, only case reports or small case series have appeared in the literature and the long-term outcome of CCP remains unknown. The aim of this study was to review cases of CCP diagnosed at our institution and to investigate their outcome. Nineteen patients given a diagnosis of CCP more than 6 years previously were identified. Their medical records and histopathologic findings were reviewed. With a median follow-up duration of 11.5 years, regression of skin lesions was observed in 85.7% of patients. Persistence of skin lesions 11.5 years after diagnosis was confirmed histopathologically in one case, with a reduction in clear cell density. Retrospective nature of the study is a limitation. No treatment is necessary for CCP because the skin lesions are asymptomatic and most patients experience at least partial regression.